Handbook of fiscal policy - Rabin, Jack; Stevens, Glenn L. (New York : Marcel Dekker, 2002)
Providing forty articles written by experts, this book explores the development of government spending and revenue policymaking, the legacy of John Maynard Keynes, taxes and tax policies, government budgeting and accounting, and government debt management. Topics include the implications of the federal balanced budget amendment, factors that affect implementation of fiscal policies, the relationship between tax assessment and economic prosperity, and debt management strategies by government institutions. It covers the role of government in formulating economic policies for growth and full employment and reviews issues associated with the implementation of fiscal policies.
This is a companion volume to Handbook of monetary policy.
Includes bibliographical references and index.
rpm 07/09/16
Loans
Keywords: Fiscal policy; Monetary policy; United States